Implementation of the Double Diamond Method in User Experience Design of Health Service Application (Homecare) - Rian, Rian Hidayat; Agung Triayudi; Ira Diana Sholihati (SaNa: Journal of Blockchain, NFTs and Metaverse Technology, 2024)
The rapid development of technology at present is almost utilized in every aspect of life, including education, economy, social, and health. However, the equal distribution of this technology has not been fully implemented, especially in the field of health. According to data from Databoks in 2022, 71% of the population has never accessed health services online. This serves as the basis for the creation of the User Interface (UI) and User Experience (UX) for health service applications (homecare) using the Double Diamond method, which is divided into four stages: discover, define, develop, and deliver. Data collection in this research is conducted through literature studies, interviews, and observations. Additionally, usability testing is performed using the System Usability Scale (SUS), with a testing result of 83.3%, categorized as excellent. This can contribute to a positive user experience for the users.